HATHA YOGA EFEKTIF MENINGKATKAN KUALITAS TIDUR LANSIA - Suparwati, Komang Tri Adi; Laksmi Patni, Gusti Ayu Putu; Jaya, I Putu Prisa; Maulana, Ida Ayu Ratih Wulansari; Novianti, I Gusti Ayu Sri Wahyuni (PHYSIO MOVE JOURNAL, 2024)
Elderly sleep quality disorders can be overcome by doing low impact exercises. Tai Chi and Hatha Yoga are types of low impact exercises with a series of smooth and slow movements that are suitable for the elderly. The purpose of knowing the effect of Tai Chi and Hatha Yoga on sleep quality in the elderly in Banjar Dakdakan, Peguyangan Village, North Denpasar District. The two group pre-test and post-test design method was carried out in April-May 2023 with a sample of 20 respondents in Banjar Dakdakan who met the inclusion and exclusion criteria. The sample was divided into two groups, namely 10 respondents in the Tai Chi Gymnastics group (Group 1) and 10 respondents in the Hatha Yoga gymnastics group (Group 2). Measurement instruments to assess sleep quality using the Pittsburgh Sleep Quality Index (PSQI) questionnaire. Data analysis with the Wilcoxon test to determine the effect of Tai Chi and Hatha Yoga exercises on sleep quality in the elderly. The results showed a value of p = 0.05 (p < 0.05) which indicates that there is a difference between group 1 and group 2 on improving sleep quality in the elderly. Keywords: elderly, sleep quality, tai_chi, hatha_yoga, PSQI ABSTRAKGangguan kualitas tidur lansia dapat diatasi dengan cara melakukan senam yang bersifat low impact. Tai Chi dan Hatha Yoga adalah jenis senam low impact dengan rangkaian gerakan yang halus dan lambat sehingga cocok dilakukan oleh lanjut usia. Tujuan mengetahui pengaruh  Tai Chi dan Senam Hatha Yoga terhadap kualitas tidur pada lansia di Banjar Dakdakan, Desa Peguyangan, Kecamatan Denpasar Utara. Metode two group pre-test and post-test design yang dilaksanakan pada bulan April-Mei tahun 2023 dengan sampel sebanyak 20 responden di Banjar Dakdakan yang telah memenuhi kriteria inklusi dan eksklusi. Sampel dibagi menjadi dua kelompok yaitu 10 responden kelompok Senam Tai Chi (Kelompok 1) dan 10 responden kelompok senam Hatha Yoga (Kelompok 2). Instrumen pengukuran untuk menilai kualitas tidur menggunakan kuisioner Pittsburgh Sleep Quality Index (PSQI). Analisis data dengan uji wilcoxon test untuk mengetahui pengaruh senam Tai Chi dan Senam Hatha Yoga kualitas tidur pada lansia. Hasil menunjukkan nilai p = 0,05 (p < 0,05) yang menunjukkan bahwa terdapat perbedaan yang antara kelompok 1 dan kelompok 2 terhadap peningkatan kualitas tidur pada lansia. Keywords: lansia, kualitas_tidur, tai_chi, hatha_yoga, PSQI